ICT, organizational communication in the management of executives - Churruca Tineo, Cristina (2021)
Technological support is relevant in the management of Executives in the administrative, pedagogical and curricular areas with a strategic guideline in organizational communication. The objective is to determine if the use of ICT, organizational communication influences the Management of the UGEL 01, 2020 Executives. The instruments were Likert scale questionnaires for the variables, submitted to the respective analysis of reliability and validity. The positivist methodology was used, a quantitative approach of a basic type of descriptive explanatory causal level of non-experimental and correlational design. The population was made up of 372 managers, whose sample was 110 managers. The results were processed in a descriptive and inferential way using tables and figures, the ordinal logistic regression test indicated a significance value of .004 less than 0.05, it concluded that the use of ICT, organizational communication in the Management of Directors has an influence of 14.5% on the management of the directors of UGEL 01, 2020.